Building Identity: Agrotourism Brand Building Strategy in Sayum Village, Sabah - Sekar Chalifah Segara; Ihsan Effendi; Adelina Lubis (Cita konsultindo, 2024)
Sayum Saba Village is one of the villages in Sibolangit District which has beautiful views and a clear river. However, the natural beauty of Sayum Saba has not been well exposed so it is not widely visited by tourists. This is very unfortunate considering that the village has natural beauty and unique culture so that it can actually become a favorite tourist destination in North Sumatra. The urgency of this research is that an appropriate marketing strategy model (brand building) is needed to increase the number of visits to Sayum Saba village agrotourism. The aim of this research is to create an appropriate marketing adaptation model for the development of agrotourism in Sayum Sabah village. Data collection includes primary and secondary data. Data was collected using literature studies, observations, interviews, and Focus Group Discussions. Data was analyzed using SWOT analysis.